Responsible internationalization: new paradigms for cooperation between higher education institutions - STALLIVIERI, Luciane; VIANNA, Cleverson Tabajara (My University, 2020)
This article provides a conceptual view of the Internationalization of Higher Education and presents some anchor points for the development of the concept of Responsible Internationalization. The centrepiece of the article is the introduction of five new dimensions to the dominant paradigm, based on the assumptions of balance, responsibility, sustainability, inclusion and compliance.

Este artigo fornece uma visão conceitual da Internacionalização do Ensino Superior e apresenta alguns pontos de ancoragem para o desenvolvimento do conceito de Internacionalização Responsável. A peça central do artigo é a introdução de cinco novas dimensões ao paradigma dominante, baseados nos pressupostos de equilíbrio, responsabilidade, sustentabilidade, inclusão e compliance.

Este artículo ofrece una visión conceptual de la Internacionalización de la Educación Superior y presenta algunos puntos de anclaje para el desarrollo del concepto de Internacionalización Responsable. La pieza central del artículo es la presentación de cinco nuevas dimensiones al paradigma dominante, basadas en los supuestos de equilibrio, responsabilidad, sostenibilidad, inclusión y compliance.
Internacionalização responsável: novos paradigmas de cooperação entre instituições de ensino superior
Keywords: Responsabilidade social; Ensino público; Intercâmbio educacional internacional; Gestão e Negócios